2010
DOI: 10.1071/ch09605
|View full text |Cite
|
Sign up to set email alerts
|

The Research Front on Molecular Logic

Alberto Credi

Abstract: The study of the logic implications of the behaviour of molecular systems stimulates the ingenuity of researchers by introducing new concepts in chemistry, and could lead to applications in fields ranging from medicine to materials science. This Research Front provides a taste of this exciting and rapidly growing research area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Since Silva’s first influential discovery indicated that fluorescent sensors could be used as logic systems, the burgeoning of molecular logic gates capable of carrying out binary arithmetic and logic calculations has drawn the attention of chemical and biological research workers. Nevertheless, most logic gates count on only one output pattern . Recently, studies have been focused on constructing logic molecules with multiple fluorescence outputs, whose functions could be modulated by the combination of multiple inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Since Silva’s first influential discovery indicated that fluorescent sensors could be used as logic systems, the burgeoning of molecular logic gates capable of carrying out binary arithmetic and logic calculations has drawn the attention of chemical and biological research workers. Nevertheless, most logic gates count on only one output pattern . Recently, studies have been focused on constructing logic molecules with multiple fluorescence outputs, whose functions could be modulated by the combination of multiple inputs.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] A further important application is represented by their use as switches and logic architectures, and excellent studies have recently been reported by van der Boom, De Silva and others. [11][12][13][14][15][16][17][18] Many surfaces can be used as substrates to fabricate monolayers and about a half of the published papers on this subject deals with thiol headgroups anchored to noble metals. 19 Despite the importance of the concerned theoretical aspects, these systems are of little practical application because of the poor temporal stability of the related metal-S bond.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] A large number of review articles are also available, including article collections in special journal issues. [41][42][43] A series of biennial conferences dedicated to the field has completed the fourth edition. 44 The first commercial product is serving worldwide in life-critical situations, 45,46 with sales of 120M $ so far.…”
Section: Introductionmentioning
confidence: 99%